Gas injection into geological formations and related topics - Wu, Ying (Petroleum engineer); Carroll, John J., 1958-; Hao, Mingqiang; Zhu, Weiyao (Advances in natural gas engineering., 2020)
"This is the eighth volume in the series, Advances in Natural Gas Engineering, focusing on gas injection into geological formations and other related topics, very important areas of natural gas engineering. This volume includes information for both upstream and downstream operations, including chapters detailing the most cutting-edge techniques in acid gas injection, carbon capture, chemical and thermodynamic models, and much more. Written by some of the most well-known and respected chemical and process engineers working with natural gas today, the chapters in this important volume represent the most state-of-the-art processes and operations being used in the field. Not available anywhere else, this volume is a must-have for any chemical engineer, chemist, or process engineer in the industry. Advances in Natural Gas Engineering is an ongoing series of books meant to form the basis for the working library of any engineer working in natural gas today"--Provided by publisher